Investigation of Antiparasitic Activity of Two Marine Natural Products, Estradiol Benzoate, and Octyl Gallate, on Toxoplasma gondii In Vitro - Lu, Daiqiang; Zhang, Nian-Zhang; Yao, Yinning; Wang, Tingting; Hua, Qianqian; Zheng, Xiaozi; Cong, Wei; Tan, Feng (Frontiers in Pharmacology, 2022)
Toxoplasmosis, caused by Toxoplasma gondii, is a common disease worldwide and could be severe and even fatal in immunocompromised individuals and fetuses. Limitation in current available treatment options drives the need to develop novel therapeutics. This study assessed the anti-T. gondii potential of 103 marine natural products. A luminescence–based β–galactosidase activity assay was used to screen the marine natural products library. Afterwards, those compounds that displayed over 70% parasite inhibition ratio were further chosen to assess their cytotoxicity. Compounds exhibiting low cytotoxicity (≥80% cell viability) were applied to evaluate the inhibition efficacy on discrete steps of the T. gondii lytic cycle, including invasion, intracellular growth and egress abilities as well as the cell cycle. We found that both estradiol benzoate and octyl gallate caused >70% inhibition of tachyzoite growth with IC50 values of 4.41 ± 0.94 μM and 5.66 ± 0.35 μM, respectively, and displayed a low cytotoxicity with TD50 values of 34.11 ± 2.86 μM and 26.4 ± 0.98 μM, respectively. Despite their defects in inhibition of invasion and egress of tachyzoite, two compounds markedly inhibited the tachyzoite intracellular replication. Flow cytometric analyses further suggested that the anti-T. gondii activity of the estradiol benzoate, rather than octyl gallate, may be linked to halting cell cycle progression of tachyzoite from G1 to S phase. Taken together, these findings suggest that both estradiol benzoate and octyl gallate are potential inhibitors for anti-T. gondii infection and support the further exploration of marine natural products as a thinkable source of alternative and active agents against T. gondii.